ANALISIS PENGARUH DIGITALISASI PAJAK TERHADAP PAJAK PENGHASILAN DI MASA PANDEMI - ,; , (Bilancia : Jurnal Ilmiah Akuntansi; Vol 7 No 2 (2023): Bilancia : Jurnal Ilmiah AkuntansiDO - 10.35145/bilancia.v7i2.2305, 2023)
ABSTRACT The challenge of digital technology can change behavior, especial in the context of taxation during pandemic. Taxes are contributed high of income. The reformation in the field of tax administrations is modernization of tax administration system. Change in digital technology are used to increase the potential of taxpayers. The growth of tax digitization is not without problems. Problems and challenges of tax digitization were becoming from human behavior, administration pattern, and pandemic. The SPI’s components were used as an analytical tool to find and map problems. The purpose of the study is determining the level of understanding of tax applications, which related to compliance and increasing taxpayers of PPh 21, and the impact of tax digitization occurs during the pandemic. The stydy has kind of qualitative research. The object of research becomes the taxpayer of PPh 21 at KPP Sleman. Sources of research data were primary and secondary. Methods and techniques of data collection were used with field techniques and library techniques. Checking the validity of the data with a credibility test had been refered to validity. Techniques for data validity had been observed, triangulated, and visited informants again. Data analysze methods are descriptive. In conclusion, DJP ensures that the server taxation products are not disturbed. Developments and improvements are needed continuously. Targeting the achievement, the number of taxpayers who fill in the survey. The improving capabilities of human resources are doing with training. Socializations are doing in direct person or online. The checking related of data are reported by taxpayers randomly. Keyword: Digitization of Taxes, E-Filling, PPh 21, Covid 19, SPI ABSTRAK Tantangan perubahan teknologi digital dapat merubah perilaku apalagi dalam konteks perpajakan di masa pandemi. Pajak adalah penyumbang pendapatan cukup tinggi. Reformasi bidang administrasi perpajakan adalah modernisasi sistem administrasi perpajakan. Perubahan teknologi digital dimanfaatkan untuk meningkatkan potensi wajib pajak. Perkembangan digitalisasi pajak bukan berarti tanpa kendala. Permasalahan dan tantangan digitalisasi pajak dari perilaku manusia, pola administrasi, serta pandemi. Komponen SPI digunakan sebagai alat analisis mencari dan memetakan permasalahan. Tujuan penelitian untuk mengetahui tingkat pemahaman aplikasi perpajakan, penerapan aplikasi perpajakan terkait kepatuhan dan peningkatan wajib pajak PPh 21, dan dampak digitalisasi pajak di masa pandemi. Merupakan jenis penelitian kualitatif. Obyek penelitian adalah wajib pajak PPh 21 di KPP Sleman. Sumber data penelitian adalah primer dan sekunder. Metode dan teknik pengumpulan data dengan teknik lapangan dan teknik kepustakaan. Pengecekan keabsahan data dengan uji kredibilitas yang mengacu pada validitas. Teknik keabsahan data dengan pengamatan, triangulasi, dan mendatangi lagi informan. Metode analisis data secara deskriptif. Kesimpulannya DJP memastikan server dari produk online perpajakan tidak mengalami gangguan. Pengembangan dan perbaikan dilakukan secara berkelanjutan. Mentargetkan capaian jumlah wajib pajak yang mengisi survei. Peningkatan kemampuan SDM yang dimiliki dengan pelatihan. Sosialisasi secara langsung ataupun daring. Pengecekan data terkait data yang dilaporkan oleh wajib pajak secara acak. Kata kunci: Digitalisasi Pajak, E-Filling, PPh 21, Covid 19, SPI